Hollow silica nanostructures with small size Au nanoparticles for catalytic applications. Issue 92 (19th September 2016) - Yao, Lin; Lee, Jong-Min
Abstract : Hollow silica nanostructures synthesized using the silica precursors (3-aminopropyl) trimethoxysilane and tetraethyl orthosilicate provide support to small sized gold nanoparticles with a high catalytic activity for the reduction of 4-nitrophenol. Abstract : Hollow silica nanostructures synthesized by adjusting the ratio between silica precursors of (3-aminopropyl) trimethoxysilane (APTMS) and tetraethyl orthosilicate (TEOS) with a micelle structure as a template provide support to small size gold nanoparticles with high catalytic activity in the reduction of 4-nitrophenol to 4-aminophenol.